Peripheral nerve injuries in weight training - Lodhia, K. R.; Brahma, B.; McGillicuddy, J. E. (The Physician and Sportsmedicine, 2005)
Direct trauma, compression caused by muscle hypertrophy or other soft tissue changes, or excessive stretching of a peripheral nerve in the upper extremity may lead to uncommon—but potentially serious—complications. Clinicians are seeing more of these injuries as weight training, power lifting, bodybuilding, cross-training, and general physical conditioning with weights become more popular. Symptoms of pain, weakness, paresthesia, or palsy; physical exam findings; electromyography; and nerve conduction studies are used to make the diagnosis. Most conditions respond well to conservative measures, such as rest from the offending exercise and correction of poor technique, but surgery may be required for complete clinical resolution in severe cases.